La profession comptable canadienne à l’heure du libre-échange - Côté, Yves-Aubert (Assurances)

(untitled) (HEC Montréal, 1989)
The author introduces his subject by observing that the Canada-U.S. Free Trade Agreement, which came into effect on January 1st of this year, gives formal recognition to the long-standing integration of our two countries. From the standpoint of the Canadian public accountancy profession he then examines the basic principles underneath the provisions of the Agreement relating to services, emphasizing that the principle of national treatment as enunciated stops short of prescribing mandatory mutual recognition and the free circulation of professionals. He speculates on the consequences of the choice to be made by the Canadian and American accountancy professions between the status quo and the pursuit of professional harmonization, outlining the principal questions to be resolved on the latter case. ln conclusion, the author urges the Canadian profession thoroughly to analyse the Agreement with a view to adopting strategies aimed at preserving Canadian identity while looking after the interests of the public.